First Step Next and homeBase: A Comparative Efficacy Study of Children With Disruptive Behavior. (January 2022) - Frey, Andy J.; Small, Jason W.; Seeley, John R.; Walker, Hill M.; Feil, Edward G.; Lee, Jon; Lissman, Dana Cohen; Crosby, Shantel; Forness, Steven R.
Disruptive behavior disorders in childhood are increasingly pervasive and associated with numerous, negative long-term outcomes. The current study examined whether adding a brief, home-visitation intervention to an existing, multi-component (child and teacher) intervention, would improve social-emotional and behavioral outcomes for young children with challenging behavior in home and school settings who required intensive support. A total of 379 teacher-parent-student triads were screened for elevated levels of behavioral risk in school and home settings and then randomly assigned to school only intervention (i.e., teacher and student components), home only intervention (i.e., parent), both combined, or business-as-usual control conditions. We examined baseline and posttest outcomes across prosocial behavior, problem behavior, and academic domains. The results demonstrated substantial support for the teacher and child-focused condition and combined conditions, and modest support for the parent-focused condition. The study advances the literature by increasing the knowledge base related to these interventions implemented alone and in combination.